Self‐Amplifying Feedbacks Accelerate Greening and Warming of the Arctic. Issue 14 (20th July 2018) - Zhang, W.; Miller, P. A.; Jansson, C.; Samuelsson, P.; Mao, J.; Smith, B.
Abstract: Increased greening, higher vegetation productivity, and shrubification have been observed in Arctic tundra in response to recent warming. Such changes have affected the near‐surface climate through opposing biogeophysical feedbacks (BF) associated with changes to albedo and evapotranspiration. However, the likely spatiotemporal variations of BF to future climate change and the consequences for Arctic vegetation and ecology have not been robustly quantified. We apply a regional Earth system model (RCA‐GUESS) interactively coupling atmospheric dynamics to land vegetation response in three potential 21st‐century radiative forcing simulations for the Arctic. We find that BF, dominated by albedo‐mediated warming in early spring and evapotranspiration‐mediated cooling in summer, have the potential to amplify or modulate local warming and enhance summer precipitation over land. The magnitude of these effects depends on radiative forcing and subsequent ecosystem responses. Thus, it is important to account for BF when assessing future Arctic climate change and its ecosystem impacts. Plain Language Summary: Arctic terrestrial ecosystems are in a state of transition due to their responses to rapid warming observed in recent decades. The changes in distribution and composition of terrestrial ecosystems may induce biogeophysical feedbacks that modulate the Arctic climate. Few studies, however, have quantified the impacts of such feedbacks by accounting for the tight coupling between physical forcing factors and transient vegetation responses to the evolving climate. Using a fully coupled regional Earth system model (RCA‐GUESS), we discern impacts of biogeophysical feedbacks on regional climates at various levels of radiative forcing. We find that feedbacks dominated by albedo‐mediated warming in early spring and evapotranspiration‐mediated cooling in summer can strongly alter the future AC changes. This study indicates that biogeophysical interactions between the Arctic climate and land vegetation may shift seasonal profiles of temperature and precipitation, and should be taken into account in future assessments of climate change and its impacts in the Arctic. Key Points: Vegetation‐climate interactions are implemented in a regional Earth system model The spatiotemporal patterns of biogeophysical feedbacks associated with ecosystem responses to future Arctic climate change are quantified Biogeophysical feedbacks modulate the future Arctic climate conditions amenable to a continuation and enhancement of current greening trends